The history of science from Augustine to Galileo - Crombie, A. C. (Dover Publications, 1995)
Richly illuminating study of the Western scientific tradition from its decay after the collapse of the Roman Empire to its full reflowering in the 17th century. Topics include the incorporation of Greek and Arabic learning, criticism of Aristotle in the later Middle Ages and the Scientific Revolution itself.